Answer:
20 - i
Step-by-step explanation:
Addition of complex numbers:In complex number addition/subtraction, add the imaginary part and add the real part separately.
The error is while adding imaginary part, you have to combine the coefficients of the imaginary numbers. So, -3 +2 will give us -1. So, the result is -i.
16 - 3i + 4+ 2i = 16 + 4 -3i + 2i
= 20 - i
Answer:
20 - i
Step-by-step explanation:
The error made during second step:
When adding or subtracting expression, we add or subtract like terms.
(16 - 3i) + (4 + 2i) get rid of parenthesis
16 - 3i + 4 + 2i add/subtract like terms
20 - i (the mistake is made here, instead of "i" they typed i^2)
if a is a set of real numbers which is bounded above and b is a set of real numbers which is bounded below then there is at most one real number in both a and b?
If a is a set of real numbers that is bounded above and b is a set of real numbers that is bounded below, there is at most one real number that can exist in both sets.
A real number is any number that can be expressed as a decimal or fraction and exists on the number line.
If a set of real numbers, represented by a, is bounded above, it means that there exists a real number, represented by M, such that all the numbers in the set are less than or equal to M. Similarly, if a set of real numbers, represented by b, is bounded below, it means that there exists a real number, represented by m, such that all the numbers in the set are greater than or equal to m.
Now, let's consider a real number, represented by x, that exists in both sets a and b. If x exists in a, it must be less than or equal to M and if x exists in b, it must be greater than or equal to m. Hence, x must satisfy both conditions: M >= x >= m.
From these conditions, it can be deduced that M and m must be equal to x. In other words, there can only be one real number that is simultaneously the greatest value in a and the smallest value in b.
To know more about real number here.
https://brainly.com/question/9876116
#SPJ4
The table shows the number of students graduating from an online university in selected year . Use a calculator to write a cubic model for the number of graduates in a given year since 2002. Then use the model to estimate the number of graduates in 2008.
There were approximately 5,184 graduates in 2008.
The cubic model is a useful tool for estimating the number of graduates in a given year, as it takes into account the trend of the data points. This allows us to make an educated guess about the number of graduates in a given year, despite not having data points for that year.The cubic model for the number of graduates from an online university since 2002 can be expressed as y = -7.8x^3 + 74.4x^2 + 437x - 9,150. Here, x is the number of years since 2002, and y is the number of graduates in that year. To estimate the number of graduates in 2008, we can plug in x = 6 into the equation, giving us y = 5,184. That is, there were approximately 5,184 graduates in 2008.
Learn more about cubic model here:
https://brainly.com/question/23134736
#SPJ4
What is the result when the number 34 is increased by 50%?
Answer: 51
Step-by-step explanation: 34 + (34/2)
34/2 = 17
34+17
=51
Answer:
51
Step-by-step explanation:
Based on the given conditions, formulate: 34 x (1 + 50%)
Convert the percentage to decimals: 34 x (1 + 0.5)
Calculate the sum or difference: 34 x 1.5
Calculate the product or quotient: 51
how do i find x pls help
In the given Quadrilateral, The measure of ∠x=110°.
what are quadrilaterals?
Quadrilaterals are four-sided polygons. They are two-dimensional shapes with four straight sides, four vertices, and four angles which have sum of 360°. Quadrilaterals can have parallel sides, opposite sides that are congruent, opposite angles that are congruent, and diagonals that bisect each other. Some examples of quadrilaterals include squares, rectangles, parallelograms, trapezoids, and rhombuses.
Now,
For given Quadrilateral
three angles given are 128°, 82° and 40° and 4th angle=x°.
To find x
As we know
Sum of all interior angles of a quadrilateral=360°
128°+82° +40° +x°=360°
x=360-250
x=110°
hence,
the measure of ∠x=110°.
To know more about Quadrilaterals visit the link
brainly.com/question/29934291
#SPJ1
Use synthetic division to find the result when 3x^4 – 16x^3 + 29x^2 - 17x - 2 is divided by x – 2
Answer:
2
Step-by-step explanation:
For all parts of this question, use function y+2=3(x+4) part A : complete the x-y table :
By evaluating the linear function we will get the complete table:
x y
-2 4
0 10
2 16
4 22
How to compete the x-y table?Here we have the linear function:
y + 2 = 3*(x + 4)
And we want to use this to complete the given table (check the image at the end of the answer).
To get that, we need to evaluate the function in the given values of x.
We can rewrite:
y = 3x + 3*4 - 2
y = 3x + 10
if x = -2
y = 3*-2 + 10 = 4
if x = 0
y = 3*0 + 10 =10
if x = 2
y = 3*2 + 10 = 16
if x = 4
y = 3*4 + 10 = 22
Then the complete table is:
x y
-2 4
0 10
2 16
4 22
Learn more about linear equations at:
https://brainly.com/question/1884491
#SPJ1
4x+5(7x-3)=9(x-5)
x=???
Answer:
i think its 3 im not sure
Step-by-step explanation:
Answer:
x = -1
Step-by-step explanation:
Given equation,
→ 4x + 5(7x - 3) = 9(x - 5)
Now the value of x will be,
→ 4x + 5(7x - 3) = 9(x - 5)
→ 4x + 35x - 15 = 9x - 45
→ 39x - 15 = 9x - 45
→ 39x - 9x = -45 + 15
→ 30x = -30
→ x = -30/30
→ [ x = -1 ]
Hence, the value of x is -1.
Simplify (2a^3a^4)^5. Show all work
Answer:
(2a^3a^4)^5 simplifies to 32a^35.
Step-by-step explanation:
To simplify (2a^3a^4)^5, we can use the properties of exponents which states that when we raise a power to another power, we can multiply the exponents. Therefore, we can rewrite the expression as:
(2a^3a^4)^5 = 2^5 * (a^3a^4)^5
Next, we can simplify the expression inside the parentheses by multiplying the exponents:
a^3a^4 = a^(3+4) = a^7
Substituting this into our expression, we get:
(2a^3a^4)^5 = 2^5 * (a^3a^4)^5 = 2^5 * a^35
Finally, we can simplify this expression by using the property of exponents that states that when we multiply two powers with the same base, we can add their exponents. Therefore, we can rewrite the expression as:
2^5 * a^35 = 32a^35
Therefore, (2a^3a^4)^5 simplifies to 32a^35.
ab-c/d has a value of 24. write the values if :-
1- a, b, c, d are all positive.
2- a, b, c, d are all negative.
3- a, b, c, d are mixed of negative and positive.
WRITE ANSWERS FOR 1, 2 AND 3
The values of ab, b - c, and c/d are 6, -1, and 4 respectively when a = 2, b = 3, c = 4 and d = 1.Using BODMAS rule, we can simplify the given expression.ab - c/d = 24
Given ab-c/d has a value of 24.Now, we have to find the value ofab, b - c, and c/d.Multiplying d on both sides, we getd(ab - c/d) = 24dab - c = 24d...(1)Now, we can find the value of ab, b - c, and c/d by substituting different values of a, b, c and d.Value of ab when a = 2, b = 3, c = 4 and d = 1ab = a * b = 2 * 3 = 6.
Value of b - c when a = 2, b = 3, c = 4 and d = 1b - c = 3 - 4 = -1Value of c/d when a = 2, b = 3, c = 4 and d = 1c/d = 4/1 = 4Putting these values in equation (1), we get6d - 4 = 24dSimplifying, we get-18d = -4d = 2/9
For more such questions on BODMAS rule
https://brainly.com/question/28832666
#SPJ8
Solve x²-3x+ 5 = 0.
A.
3+√-29
+VE
2
and
3-
2
-29
B. 3+√29 and 3-√29
O c. 3+√-11 and 3-√-11
2
2
D. 3+√11 and 3-√11
Using the quadratic formula to solve the equation x²-3x+ 5 = 0, the resultant answer is (D) 3+√11/2 and 3-√11/2.
What is the quadratic formula?The quadratic formula in elementary algebra is a formula that yields the answer to a quadratic problem.
In addition to the quadratic formula, other methods of solving quadratic equations include factoring, completing the square, graphing, and others.
A second-order equation of the form ax² + bx + c = 0 denotes a quadratic equation, where a, b, and c are real number coefficients and a 0.
So, we have the equation:
x²-3x+ 5 = 0
Now, solve it using the quadratic formula as follows:
x²-3x+ 5 = 0
a = 1
b = -3
c = 5
x = -(-3)±√(-3)² -4*1*5/2
Solve this further:
x = 3±√11/2
Therefore, using the quadratic formula to solve the equation x²-3x+ 5 = 0, the resultant answer is (D) 3+√11/2 and 3-√11/2.
Know more about the quadratic formula here:
https://brainly.com/question/1214333
#SPJ1
Correct question:
Solve x²-3x+ 5 = 0.
A.3+√-29 +VE/2 and 3- 2-29
B. 3+√29 and 3-√29
C. 3+√-11 and 3-√-11/2
D. 3+√11/2 and 3-√11/2
Alec makes jam to sell at a local farmers' market. To make last week's batch, he used 2 cups of sugar and 18 cups of berries. It was so popular that he made a larger batch this week. To make this week's batch, Alec used 4 cups of sugar and 30 cups of berries, and the jam sold out even faster. Which batch had a greater ratio of sugar to berries?
Answer:
This week's batch had the greater ratio of sugar to berries
Step-by-step explanation:
Last week's ratio was 2:18
This week's ratio was 4:30
Now, we can simplify both of these:
Divide last week's by 2:
1:9
Divide this week's by 2:
2:15
1:9 is equivalent to 0.11, and 2:15 is equivalent to 0.13
So, this week's batch had the greater ratio of sugar to berries
The batch with 4 cups of sugar and 30 cups of berries has a greater ratio of sugar to berries and is given by the proportion B = 4/30 = 0.1333
What is Proportion?The proportion formula is used to depict if two ratios or fractions are equal. The proportion formula can be given as a: b::c : d = a/b = c/d where a and d are the extreme terms and b and c are the mean terms.
The proportional equation is given as y ∝ x
And , y = kx where k is the proportionality constant
It demonstrates the equality of the relationship between the expressions printed on the left and right sides.
Given data ,
Let the proportion equation be represented as A and B
Now , for the last week's batch
Alec used 2 cups of sugar and 18 cups of berries
So , the ratio of sugar to berries is 2 : 18
The proportion is 2 / 18 = 0.1111
Now , for this week's batch
Alec used 4 cups of sugar and 30 cups of berries
So , the ratio of sugar to berries is 4 : 30
So , the proportion is 4 / 30 = 0.1333
Now , the proportion of 4 : 30 is greater than 2 : 18
Hence , this week's batch had a greater proportion
To learn more about proportion click :
https://brainly.com/question/7096655
#SPJ2
How many paths are there from $A$ to $B,$ if you travel along the edges? You can travel along each edge at most once, but you can pass through the same point more than once. (You can pass through $B,$ as long as you end up at the point $B.$)
Answer:
9
Step-by-step explanation:
You don't need to pass through each edge once.
If we name the top vertex 1 and the bottom vertex 2 then here are the possible combinations:
A-1-B
A-B
A-2-B
A-1-B-A-2-B
A-2-B-A-1-B
A-B-1-A-2-B
A-B-2-A-1-B
A-1-B-2-A-B
A-2-B-1-A-B
Some people say 6 because they think you need to pass through all the edges. But the only restriction with travelling on the edges is you can't pass one twice. The point is read the wording and it becomes easy.
Hope this helps!
Set up an equation for x and solve to the nearest degree
Answer:
Almost equals 28°
Step-by-step explanation:
cos(x)= 12/18
x= cos^-1 (12/18)
So it equals 48.1896°
Find the slope of the line.
y = -10x - 2
The slope is the change in y-axis to x-axis of a graph. The slope of the line given is -10
How to find the slope of a line?The standard equation of a line in slope intercept form is given as y = mx+b
where
m is the slopeb is the y-interceptGiven the equation y = -10x - 2
Compare
mx = -10x
m = -10
Hence the slope of the line given is -10
Learn more on slope here: https://brainly.com/question/3493733
#SPJ1
A student has 56 hours for 8 finals what amount of time will she have for each exam
Answer:
7 hours per final
Step-by-step explanation:
Take the number of hours and divide by the number of finals
56/8 = 7
7 hours per final
What is the solution
9 • x = –63?
how do it prove this without approximately calculating the logarithm ?
Answer:
\(10 < {e}^{8} \)
\( ln(10) < 8\)
\( ln(10) - 8 < 0\)
Since ln(10) > 0, it follows that ln(10) + 1 > 0, and so:
\(( ln(10) + 1)( ln(10) - 8) < 0\)
\( {( ln(10)) }^{2} - 7 ln(10) - 8 < 0\)
\(( { ln(10) })^{2} - 7 ln(10) + 1 < - 9\)
\( {( ln(10)) }^{2} + 2 ln(10) + 1 < 9 ln(10) - 9\)
\( {( ln(10) )}^{2} + 2 ln(10) + 1 < 9( ln(10) - 1)\)
(ln(10) + 1)^2 < 9(ln(10 - 1)
ln(10) + 1 < 3√(ln(10) - 1)
(1 + ln(10))/3 < √(ln(10) - 1)
√(ln(10) - 1) > (1+ ln(10))/3
21 + (-34)
Please give the answer
Answer:
=] - 13
Step-by-step explanation:
=>21+(-34)
=> 21-34
=> -13
URGENT *EASY 10 POINTS* : Show steps to get the expression ln(sqrt(2) +1) - ln(1/sqrt(2)) equal to -ln(1-(1/sqrt2))
Answer:
Step-by-step explanation:
To show that the expression \(\ln(\sqrt{2} + 1) - \ln\left(\frac{1}{\sqrt{2}}\right)\) is equal to \(-\ln\left(1 - \frac{1}{\sqrt{2}}\right)\), we can simplify both sides of the equation using the properties of logarithms. Here are the steps:
Step 1: Simplify the expression on the left side:
\(\ln(\sqrt{2} + 1) - \ln\left(\frac{1}{\sqrt{2}}\right)\)
Step 2: Apply the logarithmic property \(\ln(a) - \ln(b) = \ln\left(\frac{a}{b}\right)\) to combine the logarithms:
\(\ln\left(\frac{\sqrt{2} + 1}{\frac{1}{\sqrt{2}}}\right)\)
Step 3: Simplify the expression within the logarithm:
\(\ln\left(\frac{(\sqrt{2} + 1)}{\left(\frac{1}{\sqrt{2}}\right)}\right)\)
Step 4: Simplify the denominator by multiplying by the reciprocal:
\(\ln\left(\frac{(\sqrt{2} + 1)}{\left(\frac{1}{\sqrt{2}}\right)} \cdot \sqrt{2}\right)\)
\(\ln\left(\frac{(\sqrt{2} + 1) \cdot \sqrt{2}}{\left(\frac{1}{\sqrt{2}}\right) \cdot \sqrt{2}}\right)\)
\(\ln\left(\frac{(\sqrt{2} + 1) \cdot \sqrt{2}}{1}\right)\)
Step 5: Simplify the numerator:
\(\ln\left(\frac{(\sqrt{2} + 1) \cdot \sqrt{2}}{1}\right)\)
\(\ln\left(\sqrt{2}(\sqrt{2} + 1)\right)\)
\(\ln\left(2 + \sqrt{2}\right)\)
Now, let's simplify the right side of the equation:
Step 1: Simplify the expression on the right side:
\(-\ln\left(1 - \frac{1}{\sqrt{2}}\right)\)
Step 2: Simplify the expression within the logarithm:
\(-\ln\left(\frac{\sqrt{2} - 1}{\sqrt{2}}\right)\)
Step 3: Apply the logarithmic property \(\ln\left(\frac{a}{b}\right) = -\ln\left(\frac{b}{a}\right)\) to switch the numerator and denominator:
\(-\ln\left(\frac{\sqrt{2}}{\sqrt{2} - 1}\right)\)
Step 4: Simplify the expression:
\(-\ln\left(\frac{\sqrt{2}}{\sqrt{2} - 1}\right)\)
\(-\ln\left(\frac{\sqrt{2}(\sqrt{2} + 1)}{1}\right)\)
\(-\ln\left(2 + \sqrt{2}\right)\)
As we can see, the expression \(\ln(\sqrt{2} + 1) - \ln\left(\frac{1}{\sqrt{2}}\right)\) simplifies to \(\ln(2 + \sqrt{2})\), which is equal to \(-\ln\left(1 - \frac{1}{\sqrt{2}}\right)\).
A bag with 8 marbles has 4 red marbles, 3 blue marbles, and 1 yellow marble.A marble is chosen at random. What is the probability that it is red? Write your answer as a fraction in simplest form.
SOMEONE PLEASE HELP ME IM SO STUCK
Answer:
1/4
Step-by-step explanation:
First you add all of the marbles in the bag which is 16 marbles. The fraction of red marbles to the total would be 4/16. In the simplest form that is 1/4. You can also just do 4 divide by 16 which gives you 0.25 and in decimal form that is 1/4.
How would you solve this question or similar questions? It is solving for x.
Given the initial expression
\(\sqrt[]{2x+3}=\sqrt[]{2x}+3\)Then,
\(\begin{gathered} \sqrt[]{2x+3}=\sqrt[]{2x}+3 \\ \Rightarrow(\sqrt[]{2x+3})^2=(\sqrt[]{2x}+3)^2 \\ \Rightarrow2x+3=2x+6\sqrt[]{2x}+9 \end{gathered}\)Therefore,
\(\begin{gathered} \Rightarrow3=6\sqrt[]{2x}+9 \\ \Rightarrow-6=6\sqrt[]{2x} \\ \Rightarrow\sqrt[]{2x}=-\frac{6}{6}=-1 \\ \Rightarrow\sqrt[]{2x}=-1 \\ \Rightarrow\sqrt[]{2}\sqrt[]{x}=-1 \\ \Rightarrow\sqrt[]{x}=-\frac{1}{\sqrt[]{2}} \end{gathered}\)And sqrt(x)>=0 for any real number.
Therefore, there is no real solution to the equation.
The hypotenuse of a right triangle has length 15 and one leg has length 5. The length of the other leg is
Answer:
15.81
Step-by-step explanation:
c=a^2+b^2=5^2+15^2≈ 15.81139
find the coordinate of a triangle a(1,3) , b(2,5) and c(3,3) after being rotated about fixed point p(2,4) by 45 in clockwise direction and then translate (3,4) .
After the transformation point A will be at (5, 6.586), point B will be at (5.121, 7.121) and point C will be at (6.121, 5.121).
STEPS FOR FIND THE COORDINATEThe coordinates of a triangle after rotation and translation can be found using the following steps:
Rotation: To rotate a point (x, y) about a fixed point (a, b) by an angle θ (in this case, 45 degrees in the clockwise direction), you can use the following formulas to find the new coordinates:x' = (x - a) * cos(θ) - (y - b) * sin(θ) + a
y' = (x - a) * sin(θ) + (y - b) * cos(θ) + b
Translation: To translate a point (x, y) by a distance (dx, dy) in the x and y direction, you can use the following formulas to find the new coordinates:x' = x + dx
y' = y + dy
So for the first vertex of the triangle(1,3) after being rotated about fixed point p(2,4) by 45 in clockwise directionx' = (1 - 2) * cos(45) - (3 - 4) * sin(45) + 2 = -1.121 + 1.121 + 2 = 2.000
y' = (1 - 2) * sin(45) + (3 - 4) * cos(45) + 4 = -0.707 - 0.707 + 4 = 2.586
And after the translation (3,4) for point Ax' = 2 + 3 = 5
y' = 2.586 + 4 = 6.586
similarly for point B(2,5) will be (5.121,7.121)
and for point C(3,3) will be (6.121,5.121)
So after the transformation point A will be at (5, 6.586), point B will be at (5.121, 7.121) and point C will be at (6.121, 5.121)Learn more about coordinate of a triangle here:
https://brainly.com/question/28566332
#SPJ4
Seven more than three times a number is 25. What is the number?
Niklas is going to invest in an account paying an interest
rate of 3.2% compounded quarterly. How much would he
need to invest, to the nearest dollar, for the value of the
account to reach $5,000 in 8 years?
Answer:
Multiply it you will get it its simple
Step-by-step explanation:
1. Evaluate each expression without using a calculator.
(a) \((-3)^{4}\)
The result of the exponential expression is 81
Indices expressionsIndices are written in term of exponents
According to the expoenent law of indices
a^4 = a * a * a * a
Given the expression
(-3)^4
This means the product of -3 in four places. Mathematically
(-3)^4 = -3 * -3 * -3 * -3
(-3)^4 = 9 * 9
(-3)^4 = 81
Hence the result of the exponential expression is 81
Learn more on exponents here: https://brainly.com/question/11975096
A ship is anchored off a long straight shoreline that runs north and south. From two observation points
miles apart on shore, the bearings of the ship are
and
. What is the distance from the ship to each of the observation points? Round each answer to the nearest tenth of a mile.
The distance from the north most ship to the observation is
miles.
The distance from the south most ship to the observation is
miles.
The distance from the north most ship to the observation is 2.9 miles and the distance from the south most ship to the observation is 9.9 miles.
The bearing is defined as the angle measured clockwise from the north direction. A ship is anchored off a long straight shoreline that runs north and south.
From two observation points miles apart on shore, the bearings of the ship are 52 degrees and 134 degrees respectively. To find the distance from the ship to each of the observation points, we can use trigonometry.
Let's call the distance from the north observation point to the ship x, and the distance from the south observation point to the ship y. The bearings from the north and south observation points can be drawn as follows:
[asy]
unitsize(1cm);
pair O = (0,0), N = (-2,0), S = (2,0), A = (-2,1), B = (2,-1);
draw(O--N--A,Arrow);
draw(O--S--B,Arrow);
\(label("$52^\circ$", N + 0.3*dir(52), NE);\)
\(label("$134^\circ$", S + 0.3*dir(134), SE);\)
draw(O--A--B--cycle,dashed);
\(label("$x$", (N+A)/2, W);\)
\(label("$y$", (S+B)/2, E);\)
[/asy]
We can use the tangent function to find x and y, since we have the angle and opposite side.
From the north observation point, we have:
\($$\tan(52^\circ) = \frac{x}{2}$$$$x = 2\tan(52^\circ) \approx 2.95$$\)
From the south observation point, we have:
\($$\tan(134^\circ) = \frac{y}{2}$$$$y = 2\tan(134^\circ) \approx 9.88$$\)
Therefore, the distance from the north most ship to the observation is 2.9 miles and the distance from the south most ship to the observation is 9.9 miles.
Know more about trigonometry here:
https://brainly.com/question/13729598
#SPJ8
if f(x)=5^2x-2 and g(x)=x+1, find (f-g) (x)
The function (f-g) (x) is represented as 5^2x - 3 - x .
What is a function?The function is a type of relation, or rule, that maps one input to specific single output.
Given;
f(x)=5^2x-2
g(x)=x+1
Then, the function
(f-g) (x) = 5^2x-2 - (x+1)
Distribute the negative;
(f-g) (x) = 5^2x-2 - x - 1
(f-g) (x) = 5^2x - 3 - x
Hence, the function (f-g) (x) is represented as 5^2x - 3 - x .
Learn more about function here:
https://brainly.com/question/2253924
#SPJ1
yall please help.
Solve for x.
Answer:
I hope this will be helpful to you mark me as brainliest pls
Answer:
C
Step-by-step explanation:
- (\(\frac{28x+12}{8}\) ) < 6x - 30 ( multiply both sides by 8 to clear the fraction )
- (28x + 12) < 48x - 240 ← distribute parenthesis by - 1
- 28x - 12 < 48x - 240 ( subtract 48x from both sides )
- 76x - 12 < - 240 ( add 12 to both sides )
- 76x < - 228
divide both sides by - 76 reversing the symbol as a result of dividing by a negative quantity.
x > 3
I need help
I need help
I need help
I need help
I need help
I need help
I need help
The sequence is decreasing as n increases and sequence converges to the value 0.
The given sequence is defined as aₙ = 1 / (7n + 3).
To determine if the sequence converges or diverges, we need to analyze its behavior as n approaches infinity.
As n increases, the denominator 7n + 3 also increases which means that the values of aₙ will get smaller and smaller, approaching zero as n becomes larger.
The sequence converges to the value 0.
The sequence is decreasing as n increases.
The sequence converges to the value 0.
To learn more on Sequence click:
https://brainly.com/question/21961097
#SPJ1